Construction of PdCu Alloy Decorated on the N-Doped Carbon Aerogel as a Highly Active Electrocatalyst for Enhanced Oxygen Reduction Reaction - Yangxin Bai; Wenke Hao; Aleeza Altaf; Jiaxin Lu; Liu Liu; Chuanyong Zhu; Xindi Gu; Xiaodong Wu; Xiaodong Shen; Sheng Cui; Xiangbao Chen (Gels)
Fuel cells/zinc–air cells represent a transformative technology for clean energy conversion, offering substantial environmental benefits and exceptional theoretical efficiency. However, the high cost and limited durability of platinum-based catalysts for the sluggish oxygen reduction reaction (ORR) at the cathode severely restrict their scalability and practical application. To address these critical challenges, this study explores a groundbreaking approach to developing ORR catalysts with enhanced performance and reduced costs. We present a novel Pd3Cu alloy, innovatively modified with N-doped carbon aerogels, synthesized via a simple self-assembly and freeze-drying method. The three-dimensional carbon aerogel-based porous structures provide diffusion channels for oxygen molecules, excellent electrical conductivity, and abundant ORR reaction sites. The Pd3Cu@2NC-20% aerogel exhibits a remarkable enhancement in ORR activity, achieving a half-wave potential of 0.925 V, a limiting current density of 6.12 mA/cm2, and excellent long-term stability. Density functional theory (DFT) calculations reveal that electrons tend to transfer from the Pd atoms to the neighboring *O, leading to an increase in the negative charge around the *O. This, in turn, weakens the interaction between the catalyst surface and the *O and optimizes the elementary steps of the ORR process.